2020
DOI: 10.1038/s41598-020-69232-3
|View full text |Cite
|
Sign up to set email alerts
|

RNA-sequencing analysis revealed genes associated drought stress responses of different durations in hexaploid sweet potato

Abstract: Purple-fleshed sweet potato (PFSP) is an important food crop, as it is a rich source of nutrients and anthocyanin pigments. Drought has become a major threat to sustainable sweetpotato production, resulting in huge yield losses. Therefore, the present study was conducted to identify drought stressresponsive genes using next-generation (NGS) and third-generation sequencing (TGS) techniques. Five cDNA libraries were constructed from seedling leaf segments treated with a 30% solution of polyethylene glycol (PEG-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 92 publications
(100 reference statements)
2
21
0
Order By: Relevance
“…The solcap_snp_c1_13430 in chromosome 1 was associated with the ÎČ‐amylase gene (ID Soltu.DM.01G022570). Previous authors related the ÎČ‐amylase activity with drought tolerance in potatoes (Schafleitner et al., 2007; Watkinson et al., 2008), sweet potatoes (Arisha et al., 2020) and Arabidopsis thaliana (Prasch et al., 2015; Zanella et al., 2016). The ÎČ‐amylase activity is involved in the starch catabolic process and the ÎČ‐amylase ‐mediated starch breakdown in guard cells can lead to improved plant performance under drought stress (Arisha et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The solcap_snp_c1_13430 in chromosome 1 was associated with the ÎČ‐amylase gene (ID Soltu.DM.01G022570). Previous authors related the ÎČ‐amylase activity with drought tolerance in potatoes (Schafleitner et al., 2007; Watkinson et al., 2008), sweet potatoes (Arisha et al., 2020) and Arabidopsis thaliana (Prasch et al., 2015; Zanella et al., 2016). The ÎČ‐amylase activity is involved in the starch catabolic process and the ÎČ‐amylase ‐mediated starch breakdown in guard cells can lead to improved plant performance under drought stress (Arisha et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We further determined the role of OsPIP2;2 in the plant resistance to a physiological drought stress caused by Polyethylene glycol 6,000 (PEG 6000 ). PEG with molecular mass 4,000-8,000 effectively induces physiological drought in a variety of plant species, and PEG 6000 has been mostly used (Arisha et al, 2020;Dong et al, 2005;Hajihashemi & Geuns, 2016;Huang et al, 2019;Ren et al, 2019;Tiwari et al, 2020;Zhang et al, 2017). While PEG induces drought syndromes from leaf wilting to plant collapse, plants in this process may defend themselves by activating the drought tolerance pathway to preserve water relations (Dong et al, 2005;Zhang et al, 2017 PEG 6000 was used as an inducer of physiological drought stress (Dong et al, 2005;Dubois & InzĂ©, 2020) and applied to 15-day-old rice seedlings.…”
Section: Ospips Substratesmentioning
confidence: 99%
“…Integrative approaches for large-scale transcriptomic studies have shown that responses include mainly two sets of genes, one directly involved in protecting cells from stress and the other including regulatory proteins that modulate gene expression. The first group includes water channel proteins and membrane transporters [9], key enzymes for osmolyte biosynthesis (e.g., proline, sugars) [10], detoxification enzymes (e.g., catalase, superoxide dismutase, ascorbate peroxidase) [8], enzymes for fatty acid metabolism, ferritin, and lipid-transfer proteins [11], and proteins for the protection of macromolecules (e.g., late embryogenesis abundant, antifreeze proteins and chaperones) [12]. A second important group of responsive drought-induced genes that are activated by drought include transcription factors (TFs) as the widely known dehydration responsive element binding (DREB) TFs, as well as protein kinases and phosphatases implicated in the regulation of the stress signal transduction to subsequent components in the pathway towards the nucleus [13][14][15].…”
Section: Introductionmentioning
confidence: 99%